2013
DOI: 10.1161/circulationaha.112.001094
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aortic Valve Replacement on Outcome of Symptomatic Patients With Severe Aortic Stenosis With Low Gradient and Preserved Left Ventricular Ejection Fraction

Abstract: P=0.22). Conclusions-AVR Ozkan et al AVR and Low-Gradient Severe AS 623We sought to compare the outcome of LGSAS patients who underwent AVR with those who received medical therapy. Methods Patient SelectionWe studied 1745 patients with symptomatic severe AS, based on AVA ≤1 cm 2 /m 2 , referred to our center from 2006 to 2011 for highrisk AS management (including possible valve replacement with either transcatheter AVR [TAVR] or surgical AVR [SAVR]). After exclusion of 157 patients with severe mitral or aorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(62 citation statements)
references
References 24 publications
5
53
2
2
Order By: Relevance
“…The data published in the literature, [3][4][5]7,9,11,13,14 including those of the present study, 6 suggest that symptomatic patients with paradoxical LF/LG and evidence of severe AS should undergo AVR, whereas asymptomatic patients should probably be treated conservatively and followed closely. Regardless of the therapeutic decision described above (AVR versus conservative), patients with paradoxical LF/LG should be systematically screened for the presence of abnormal arterial hemodynamics, and, depending on the results of this screening, antihypertensive therapy should be instituted or optimized.…”
Section: Challenges In the Management Of Paradoxical Lf/ Lg Assupporting
confidence: 52%
See 1 more Smart Citation
“…The data published in the literature, [3][4][5]7,9,11,13,14 including those of the present study, 6 suggest that symptomatic patients with paradoxical LF/LG and evidence of severe AS should undergo AVR, whereas asymptomatic patients should probably be treated conservatively and followed closely. Regardless of the therapeutic decision described above (AVR versus conservative), patients with paradoxical LF/LG should be systematically screened for the presence of abnormal arterial hemodynamics, and, depending on the results of this screening, antihypertensive therapy should be instituted or optimized.…”
Section: Challenges In the Management Of Paradoxical Lf/ Lg Assupporting
confidence: 52%
“…6,7,9 However, one cannot exclude that a proportion of the patients with NF/LG, and particularly of those included in categories 2 and 3 mentioned above, have true severe AS and may thus benefit from AVR. To this effect, Dumesnil et al 5 and Ozkan et al 14 reported that patients with NF/LG treated medically have poor outcomes and that AVR is associated with improved survival in both LF/LG and NF/LG AS. As opposed to other studies, 6,7,9 these 2 studies 5,14 have used an indexed AVA <0.6 cm 2 /m 2 instead of an AVA <1.0 cm 2 as inclusion criteria, therefore excluding patients having a low gradient attributable to a small body size (i.e., category 1).…”
Section: Nf/lg As: a Heterogeneous Entitymentioning
confidence: 99%
“…Several studies 10,14,[26][27][28][29][30][31] published recently provide further support for this recommendation.…”
Section: Therapeutic Managementmentioning
confidence: 86%
“…9,10 In addition, risk-stratification in patients with low-gradient severe AS (paradoxical severe AS) may be clinically challenging, especially as there are limited reports of outcome in these patients. 11 The aim of this study was to assess the utility of LV-GLS in Background-We sought to assess the utility of left ventricular global longitudinal strain (LV-GLS) in predicting mortality in moderate to severe and paradoxical severe aortic stenosis (AS) patients with preserved ejection fraction. Methods and Results-We studied 395 AS patients (70±14 years, 57% men) with aortic valve area <1.3 cm 2 evaluated between January to June 2008 (excluding severe other valve disease and LV ejection fraction <50%).…”
Section: Clinical Perspective On P 945mentioning
confidence: 99%